Motivation and Constraints of Newly Entrepreneur at 40s - Anak Agung Alvian Prasetya Putera; Usep Suhud; Agung Dharmawan Buchdadi (Profesional Muda Cendekia Publishing, 2022)
This study aims to identify the motivations and constraints of new entrepreneurs in their 40s in Jabodetabek. This study was conducted using a qualitative approach. The authors used the grounded theory approach. Researcher resources were taken based on the purposive sampling method. The collection techniques used by the researchers were observation, in-depth interviews, and documentation. The data analysis used was Nvivo12. Based on the results of a qualitative study using a grounded theory approach regarding the motivation, constraints, and efforts to resolve the barriers of new entrepreneurs in the 40s, some conclusions can be made regarding the motivation of new entrepreneurs in their 40s including (1) underlying. Motivation for entrepreneurs. Starting in their 40s to start a business is self-actualization. This motivation is based on the desire of new entrepreneurs in their 40s to advance themselves to be better than the previous situation and condition. (2) the motivation that drives new entrepreneurs in their 40s to start a business is the motivation to want to progress. The entrepreneur desires to change the fate of those who initially worked in the company or are housewives. This motivation is based on the desire to change for the better. In terms of constraints and efforts to resolve the constraints of new entrepreneurs in their 40s, the authors cover (1) Constraints in business management, including human resources, capital, and infrastructure. Efforts made by new entrepreneurs in their 40s to solve business management problems are collaborative efforts, capital management, and network expansion. (2) Constraints on own-self. The age factor is a significant issue new entrepreneurs face in their 40s. Efforts are being made to improve the self-quality of new entrepreneurs in their 40s.